1984
DOI: 10.1002/zaac.19845130604
|View full text |Cite
|
Sign up to set email alerts
|

Heteronukleare Metallatomcluster der Typen X4−n[SnM(CO)4P(C6H5)3]n und M2(CO)8 [μ‐Sn(X)M (CO)4P(C6H5)3]2 aus Umsetzungen von SnX2 mit M2(CO)8[P(C6H5)3]2 (X = Halogen; M = Mn, Re; n = 2, 3)

Abstract: Die Verbindungen der beiden Typen X4−n[SnM(CO)4P(C6H5)3]n (n = 3; M = Mn; X = F, Cl, Br, I. n = 2; M = Mn, Re; X = Cl, Br, I) sowie M2(CO)8[μ‐Sn(X)M(CO)4P(C6H5)3]2 (M = Mn; X = Cl, I. M = Re; X = Cl, Br, I) werden durch die Umsetzung von SnX2 mit M2(CO)8[P(C6H5)3]2 (M = Mn, Re) dargestellt. Ihre IR‐Bandenlagen werden zugeordnet. Das zentrale Molekülfragment von Re2(CO)8[μ‐Sn(Cl)Re(CO)4P(C6H5)3]2 besteht aus einem planaren Re2Sn2‐Rhombus mit einer transannularen ReRe‐Bindung von 316,0(2) pm. Neben den beiden R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Very few examples of rhenium−tin complexes have been reported to date . The new dirhenium-ditin complex Re 2 (CO) 8 (μ-SnPh 2 ) 2 ( 10 ) was obtained in a 52% yield from the reaction of Re 2 (CO) 8 [μ-η 2 -C(H)C(H)Bu n ](μ-H) with an excess of Ph 3 SnH at 68 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Very few examples of rhenium−tin complexes have been reported to date . The new dirhenium-ditin complex Re 2 (CO) 8 (μ-SnPh 2 ) 2 ( 10 ) was obtained in a 52% yield from the reaction of Re 2 (CO) 8 [μ-η 2 -C(H)C(H)Bu n ](μ-H) with an excess of Ph 3 SnH at 68 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Tin is widely used as a modifier for transition metal catalysts to improve their reactivities and product selectivities. , We have recently shown that Ph 3 SnH is a good reagent for the introduction of large numbers of phenyl-substituted tin ligands into carbidopentaruthenium carbonyl complexes . Surprisingly, there are very few examples of polynuclear rhenium carbonyl cluster complexes containing tin ligands . We have now found that Ph 3 SnH also reacts with the reactive rhenium complex Re 2 (CO) 8 (μ-H)[μ-C(H)C(H)Bu] to yield the new dirhenium−ditin complex Re 2 (CO) 8 (μ-SnPh 2 ) 2 , 1 , in 52% yield when allowed to react in hexane solvent at reflux for 2 h .…”
mentioning
confidence: 92%